Motives For Social Media Use (A Descriptive Study of Followers The Tiktok Account @Gerryanodv) - Trijayanto, Danang; Muhammad, Idrus (DAS Institute, 2025)
TikTok influencer @gerryanodv uses the TikTok social media platform to share fitness content and motivate followers. The problem formulation in this study is